Secrecy Analysis in Visible Light Communication Systems with Randomly Located Eavesdroppers - Cho, S; Chen, G; Coon, J (Institute of Electrical and Electronics Engineers, 2017)
We investigate the secrecy connectivity in visible light communication in the presence of randomly located eavesdroppers. We apply spatial point processes to characterize the unknown eavesdropper locations. The closed-form of the secrecy outage probability is derived as a function of the density of eavesdroppers. The analysis is verified by Monte Carlo simulations. Furthermore, we suggest an LED transmitter selection scheme based on the location of a legitimate user. It is verified that the proposed transmission scheme can significantly improve the secrecy performance as a function of the number of LED transmitters.